Development of an IOC Model Based Learning Implementation Plan to Improve Student Learning Outcomes in Class V MI Al Ihsan Kalikejambon (SCHOOLAR: Social and Literature Study in Education, 2022)
Education is a means to create a learning atmosphere and learning process so that students are active in developing their potential to have the power of self-control, personality and skills given to themselves and the community. The aim is to know how the process of using RPP based on the IOC model is. RPP is a plan that describes procedures, and organizing learning to achieve a defined basic competency. This research is a development research which is also known as Research and Development. As well as the application of the Inside Outside Circle (IOC) learning model to the Fiqh subject in class V MI Al-Ihsan Kalikejambon Tembelang Jombang. The results of the implementation of the IOC model-based learning were declared suitable for use by material experts with a validity result of 4.34. The post test results with a value of 84.1 indicate a better improvement than the pre test results with a value of 48.9. The results of student responses to the IOC learning model are very good, namely 75.83% with good categories.